(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Wanda IF, Djuita NR, Chikmawati T. 2021. Molecular phylogenetics of Malesian Diospyros (Ebenaceae) based trnL-F spacer sequences. Biodiversitas 22: 4106-4114. Diospyros is a genus composed of potential species as an economic commodity with high diversity. However, there is limited information on the phylogenetic relationship of this genus in the Malesian region. This study aimed to provide information on the species diversity through a DNA barcoding approach and revealing the phylogenetic information of Diospyros spp. in the Malesian region. This study used 20 Diospyros accessions from Bogor Botanical Garden collections, 40 Diospyros accessions, and four outgroup accessions obtained from the NCBI database. The DNA barcoding primer utilized comes from plastids, trnL-F intergenic spacer. The phylogenetic trees were constructed using the Maximum-Parsimony method. A total of 20 accessions of Diospyros were validated with sequence data on the genebank. The result showed that all accessions had relationships with 44 other Diospyros species globally. Here, we reported 10 new trnL-F intergenic spacer sequences of Malesian Diospyros species. A phylogenetic tree grouped 64 monophyletic Diospyros species into seven clades. The phylogenetic results supports the biogeographic hypothesis: the Malesian region, the Malesian-Caledonian Region, and Cosmopolite species in almost all bioregions.